2010
DOI: 10.3340/jkns.2010.48.1.85
|View full text |Cite
|
Sign up to set email alerts
|

A Solitary Skull Lesion of Syphilitic Osteomyelitis

Abstract: We experienced a rare case of solitary syphilitic osteomyelitis of the skull without any other clinical signs or symptoms of syphilis. A 20-year-old man was referred due to intermittent headache and mild tenderness at the right parietal area of the skull with a palpable coin-sized lesion of softened cortical bone. On radiological studies, the lesion was a radiolucent well enhanced mass (17 mm in diameter). The erythrocyte sedimentation rate (52 mm/h) and C-reactive protein (2.24 mg/dL) were elevated on admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…While full certainty can hardly be achieved even combining all these methods, a detailed analysis of skull and bone lesions is still considered the most reliable method for identification of acquired syphilis in past populations (Ortner, 2009). In this case, the CT appearance of our specimen (Figure 6) is very similar to images which have been reported by Gurland et al (2001) and Huang et al (2007) in HIV-infected patients with acquired syphilis; and also by Kang et al (2010) in a patient with confirmed T. pallidum infection. This morphological appearance has been previously reported as characteristic of acquired treponemal infection on radiographic and palaeopathological assessments (Thompson and Preston, 1952;Ortner, 2003;Shang and Trinkaus, 2008;Boone et al, 2009;Reinus, 2010).…”
Section: Discussionsupporting
confidence: 73%
“…While full certainty can hardly be achieved even combining all these methods, a detailed analysis of skull and bone lesions is still considered the most reliable method for identification of acquired syphilis in past populations (Ortner, 2009). In this case, the CT appearance of our specimen (Figure 6) is very similar to images which have been reported by Gurland et al (2001) and Huang et al (2007) in HIV-infected patients with acquired syphilis; and also by Kang et al (2010) in a patient with confirmed T. pallidum infection. This morphological appearance has been previously reported as characteristic of acquired treponemal infection on radiographic and palaeopathological assessments (Thompson and Preston, 1952;Ortner, 2003;Shang and Trinkaus, 2008;Boone et al, 2009;Reinus, 2010).…”
Section: Discussionsupporting
confidence: 73%
“…Syphilitic osteomyelitis usually occurs as multiple lesions, and solitary lesion was rarely reported . Our patient did not have tenderness and swelling unlike earlier published cases .…”
contrasting
confidence: 56%
“…Infectious conditions like syphilis (Kang et al , ) or tuberculosis (Raut et al , ; Dawson and Robson Brown, ) can affect the skull causing solitary round lytic lesions, although not ectocranially.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious conditions like syphilis (Kang et al, 2010) or tuberculosis (Raut et al, 2004;Dawson and Robson…”
Section: Discussionmentioning
confidence: 99%